ARABIDOPSIS THALIANA HOMEOBOX25 Uncovers a Role for Gibberellins in Seed Longevity . Issue 2 (12th December 2013) - Bueso, Eduardo; Muñoz-Bertomeu, Jesús; Campos, Francisco; Brunaud, Veronique; Martínez, Liliam; Sayas, Enric; Ballester, Patricia; Yenush, Lynne; Serrano, Ramón
Abstract : A transcription factor increases gibberellin biosynthesis and improves seed longevity . Abstract: Seed longevity is crucial for agriculture and plant genetic diversity, but it is limited by cellular damage during storage. Seeds are protected against aging by cellular defenses and by structures such as the seed coat. We have screened an activation-tagging mutant collection of Arabidopsis ( Arabidopsis thaliana ) and selected four dominant mutants with improved seed longevity ( isl1-1D to isl4-1D ) under both natural and accelerated aging conditions. In the isl1-1D mutant, characterized in this work, overexpression of the transcription factor ARABIDOPSIS THALIANA HOMEOBOX25 (ATHB25; At5g65410) increases the expression of GIBBERELLIC ACID3-OXIDASE2, encoding a gibberellin (GA) biosynthetic enzyme, and the levels of GA1 and GA4 are higher (3.2- and 1.4-fold, respectively) in the mutant than in the wild type. The morphological and seed longevity phenotypes of the athb25-1D mutant were recapitulated in transgenic plants with moderate (4- to 6-fold) overexpression of ATHB25 . Simultaneous knockdown of ATHB25, ATHB22, and ATHB31 expression decreases seed longevity, as does loss of ATHB25 and ATHB22 function in a double mutant line. Seeds from wild-type plants treated with GA and from a quintuple DELLA mutant (with constitutive GA signaling) are more tolerant to aging, providing additional evidence for a role of GA in seed longevity. A correlation was observed in several genotypes between seed longevity and mucilage formation at the seed surface, suggesting that GA may act by reinforcing the seed coat. This mechanism was supported by the observation of a maternal effect in reciprocal crosses between the wild type and the athb25-1D mutant.